Gingivektomi Sebagai Perawatan Kesimetrisan Margin Gingival: Gingivectomy as a Treatment for Gingival Margin Symmetry - Supriatna, Andi (Chakra Brahmanda Lentera Institute, 2025)
Gingival enlargement is an abnormal overgrowth of the gum tissue caused by factors such as inflammation, medications, or systemic conditions. This condition often leads to aesthetic concerns, especially when it involves the anterior region. The aim of this case report is to describe the management of gingival enlargement using conventional gingivectomy to achieve symmetrical gingival margins. This case report involved a 39-year-old female patient who complained of asymmetry in the upper anterior gingiva. After initial treatment with scaling and pocket depth evaluation, conventional gingivectomy was performed on teeth 11, 12, and 22. The procedure followed standard steps including aseptic preparation, anesthesia, tissue excision, irrigation, placement of periodontal pack, and post-operative instructions. Evaluation at the first and fourth weeks post-surgery revealed favorable healing without pain, bleeding, or edema. The gingiva appeared clinically healthy and symmetrical, with no signs of recurrence. Conventional gingivectomy is an effective treatment choice for managing gingival enlargement that affects aesthetics. It enables restoration of gingival symmetry with satisfactory healing and outcomes both functionally and cosmetically. Conventional gingivectomy in this case successfully improved gingival symmetry and resulted in optimal aesthetic outcomes without complications.